2002
DOI: 10.1215/s1522851702000091
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of temozolomide in patients with newly diagnosed supratentorial malignant glioma before radiation therapy

Abstract: Temozolomide is a novel second-generation oral alkylating agent with demonstrated ef cacy and safety in patients with recurrent glioblastoma multiforme (GBM) and anaplastic astrocytoma (AA). A multicenter phase II trial was conducted to determine the ef cacy and safety of temozolomide before radiotherapy in patients with newly diagnosed GBM and AA. Fifty-seven patients (51 adult, 6 pediatric) with newly diagnosed supratentorial GBM or AA were treated with temozolomide (200 mg/m 2 per day for 5 consecutive days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Gilbert et al [37] reported on 36 glioblastoma patients receiving standard-dose TMZ for up to four cycles. A complete response was observed in four patients and a partial response in 11 patients, for an overall response rate of 42% with a median PFS survival of 4 months and overall survival of 13 months.…”
Section: Temozolomide For Patients With Newly Diagnosed Glioblastomamentioning
confidence: 99%
“…Gilbert et al [37] reported on 36 glioblastoma patients receiving standard-dose TMZ for up to four cycles. A complete response was observed in four patients and a partial response in 11 patients, for an overall response rate of 42% with a median PFS survival of 4 months and overall survival of 13 months.…”
Section: Temozolomide For Patients With Newly Diagnosed Glioblastomamentioning
confidence: 99%
“…The rationale behind this approach is to defer potentially severe long-term neurotoxic effects induced by CNS irradiation [20,21] and to facilitate the delivery of chemotherapeutic agents to the tumor site through non-altered blood vessels. Administration of TMZ before radiation therapy to patients with newly diagnosed glioblastoma or anaplastic astrocytoma induced a high radiographic response rate, but the effects were often only short-lived [22]. In the pivotal NOA-04 trial on sequential radiochemotherapy, comparing initial radiotherapy with chemotherapy [procarbacine, CCNU and vincristine (PCV) or TMZ], chemotherapy yielded statistically equivalent efficacy as compared to radiotherapy concerning time to treatment failure (which includes firstline and first relapse treatment) as well as progression-free survival (PFS) [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its penetrance in the central nervous system could be useful in the setting of brain metastases [17]. The results of temozolomide treatment in a few cases of central nervous system germinoma refractory to conventional chemotherapy are reported in the literature [18], and at least 1 patient achieved stable disease [19]. Kondagunta et al [20], however, did not find any response in a series of 14 patients with cisplatin-refractory germ cell tumors.…”
Section: Discussionmentioning
confidence: 99%